2010
DOI: 10.3109/13550284.2010.497806
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the spike glycoprotein of human coronavirus OC43 modulate disease in BALB/c mice from encephalitis to flaccid paralysis and demyelination

Abstract: The etiology of most neurodegenerative diseases of the central nervous system remains unknown and likely involves a combination of genetic susceptibility and environmental triggering factors. Given that exposure to numerous infectious pathogens occurs during childhood, and that some viral infections can lead to neurodegeneration and demyelination, it is conceivable that some viruses may act as triggering factors in neuropathogenesis. We have previously shown that the prototype OC43 strain of the common cold-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
74
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(81 citation statements)
references
References 42 publications
7
74
0
Order By: Relevance
“…The spike protein (S) is a large type 1 transmembrane glycosylated protein responsible for recognition of the cellular receptor used by the virus to infect a susceptible cell (Cavanagh, 1995). During infection of susceptible hosts, the S protein represents an important factor of virulence as it appears to be associated with most of the cytotoxic effects that lead to degeneration of infected cells following infection by different coronaviruses (Brison et al, , 2014Favreau et al, 2009Favreau et al, , 2012Iacono et al, 2006;Jacomy et al, 2010;Phillips et al, 1999Phillips et al, , 2002.…”
Section: Viral Molecular Determinants Of Pathogenesismentioning
confidence: 99%
See 3 more Smart Citations
“…The spike protein (S) is a large type 1 transmembrane glycosylated protein responsible for recognition of the cellular receptor used by the virus to infect a susceptible cell (Cavanagh, 1995). During infection of susceptible hosts, the S protein represents an important factor of virulence as it appears to be associated with most of the cytotoxic effects that lead to degeneration of infected cells following infection by different coronaviruses (Brison et al, , 2014Favreau et al, 2009Favreau et al, , 2012Iacono et al, 2006;Jacomy et al, 2010;Phillips et al, 1999Phillips et al, , 2002.…”
Section: Viral Molecular Determinants Of Pathogenesismentioning
confidence: 99%
“…Making use of another mouse model, we showed that HCoV-OC43 induced immune cell infiltration and cytokine production within the mouse CNS. This immune response was significantly increased after infection by virus variants which harbor mutations in the surface viral glycoprotein (S), consequent of viral persistent infection of human neural cells (Jacomy et al, 2010), and which induce glutamate excitotoxicity (Brison et al, , 2014. The increased cytokine production following infection by the S-mutant viruses may induce direct damage to neurons (Amor et al, 2010) and/or disturb glutamate homeostasis by down-regulating the glutamate transporter GLT-1 on astrocytes that should recapture the excess of glutamate, which may generate glutamate excitotoxicity (Carmen et al, 2009) and thereby contribute to neuronal degeneration (Fig.…”
Section: Mechanisms Of Hcov-induced Neurodegeneration: Possible Assocmentioning
confidence: 99%
See 2 more Smart Citations
“…It is likely that strong microglial activation can trigger bystander damage, as they can release large amounts of cytokines and chemokines. In fact, we have recently shown that infection of susceptible mice by HCoV-OC43 induced the production of high level of numerous proinflammatory cytokines such as tumor necrosing factor (TNF)-alpha, interleukin (IL)-1 beta and IL-6, released in the CNS, as well as chemokines and strong infiltration of immune cells (Jacomy et al, 2010). This is again of particular interest since accumulating evidence show that these types of factors may influence the degree of encephalitis.…”
Section: Animal Model To Understand the Human Coronavirus Infectionmentioning
confidence: 99%